What can postcolonial theory contribute to the study of social equity?. (12th July 2022) - Bhati, Abhishek
Abstract: There is a unanimous agreement among scholars that social equity scholarship is essential to the study of public administration. One area of weakness in the social equity literature is its inability to develop a theoretical understanding of the complexities of race, gender, and ethnicity. This viewpoint addresses the call of Pandey, Bearfield, and Hall (2022), arguing "concept of race in public administration remains woefully undertheorized" by exploring key tenets of Postcolonial theory. Postcolonial theory can bolster social equity literature by providing a much‐needed theoretical framework to systematically understand the marginalization and subordination of people of color for centuries through representation, production of knowledge, and power. The postcolonial theory also challenges the portrayal of all non‐White minorities as one collective hegemonic identity and, therefore, can provide a sound theoretical grounding to social equity scholarship. Evidence for Practice: There is a growing call among scholars and practitioners to conceptualize race in public administration using more complex historical foundations capturing nuances of gender, ethnicity, and skin‐tone rather than simplifying race as binary (White vs. non‐White). Postcolonial theory provides a strong theoretical foundation to understand race and intersectional identity and provides a firm capacity to understand race relationships using the historical lens. Postcolonial theory also provides insights into the exploitation and subjugation of colonial subjects (citizens once colonized by European empires) and how their identity is forever molded by the slave trade and exploitation of natural resources of countries in Asia, Africa, and Latin America. Finally, the postcolonial theory provides a strong parallel between the colonial representation of the colonized subjects as the "Other" and the portrayal of poor people from the global South as stereotypical and helpless and refugees and immigrants as dangerous or "bad hombres ."